Realisasi dan Analisis Strategi Pengelolaan CSR Pasca Pandemi Covid-19 di PT. Patiware - Sesario, Revi; Sutignya, Th. Candra Wasis Agung; Febtysiana, Nur Fajar (Politeknik Negeri Pontianak, 2023)
PT Patiware is one of KPN GRUP's subsidiaries engaged in oil palm plantation and palm oil processing. As a company that complies with the principles of good corporate governance and applicable regulations, namely Article 74 of the Law of the Republic of Indonesia No. 40 of 2007 and Government Regulation No. 47 of 2012, it is required to carry out CSR activities. This study uses a quantitative descriptive approach to determine the development of CSR programs at PT Patiware over the past three years. Data was collected through questionnaires and in-depth interviews covering the following aspects: Resources, Bureaucratic Structure, Communication and Implementation Mechanism to determine the implementation of CSR strategies using SWOT analysis. The results showed that the SWOT strategy implemented according to the S-O (strengths - opportunities) model is to utilize all strengths to maximize opportunities. In 2021-2023, there were 35 CSR activities carried out by the company, of which 33 types or 94.28% were dominated by charity and 2 types or 5.72% by empowerment.